Financial Transparency and Stakeholder Governance in ESG Reporting Research: A Bibliometric Perspective - Dian Purnama Sari; Suginam Suginam; Vina Winda Sari; Rizky Indra Saputra (Graha Mitra Edukasi, 2025)
This study aims to analyze the development of research on financial transparency, stakeholder governance, and ESG reporting through a bibliometric approach using data indexed in the Scopus database. The increasing global attention toward sustainability disclosure, corporate accountability, and stakeholder-oriented governance has encouraged rapid growth in ESG-related studies across various disciplines. This research applies bibliometric analysis to identify publication trends, dominant subject areas, leading journals, influential authors, collaboration networks, keyword dynamics, co-citation structures, and thematic evolution within the literature. The findings indicate that research on ESG governance and financial transparency has experienced significant growth, particularly after 2020, reflecting the rising importance of sustainability governance and responsible corporate practices in global business environments. The results also show that the dominant research themes include ESG disclosure, sustainability reporting, corporate governance, stakeholder accountability, green finance, and digital auditing. Furthermore, the study reveals that ESG governance research has become increasingly interdisciplinary by integrating perspectives from accounting, finance, sustainability, ethics, and technological innovation. Scientific collaboration among researchers and institutions from different countries also demonstrates the growing internationalization of sustainability governance research. In addition, emerging themes such as artificial intelligence, digital financial auditing, and sustainability assurance are becoming increasingly relevant within the ESG reporting landscape. This study contributes theoretically by strengthening the integration of stakeholder theory and legitimacy theory in sustainability governance research. Practically, the findings provide insights for corporations, regulators, and policymakers in improving transparency, governance quality, and sustainability reporting practices to support long-term organizational sustainability and stakeholder trust.